2016
DOI: 10.1021/acs.orglett.6b02371
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Total Syntheses of Aetheramides and Their Stereoisomers: Stereochemical Assignment of Aetheramides

Abstract: The concise total syntheses of the potent HIV inhibitors aetheramides A and B (IC50 values of 15 and 18 nM), as well as three pairs of their stereoisomers, were achieved, which allowed the complete stereochemical assignment of aetheramides for the first time. With a longest linear sequence of 15 steps, the convergent, fully stereocontrolled route provided aetheramides A and B in 5.3% and 3.6% yields, respectively. The synthetic strategy features efficient Stille coupling for macrocyclization, asymmetric aldol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…Notably, the structure of 3 m was confirmed by its single crystal X‐ray diffraction analysis . This is in consistence with what has been observed by Li et al in a Rh(III)‐catalyzed synthesis of indoles from the reactions of imidamides with diazo ketoesters via C−H activation and C−C/C−N bond cleavage . As a further aspect, in addition to 2‐phenylindoles, 2‐(naphthalene‐1‐yl)indole was also suitable for this reaction to give 3 p in 52% yield.…”
Section: Figuresupporting
confidence: 86%
“…Notably, the structure of 3 m was confirmed by its single crystal X‐ray diffraction analysis . This is in consistence with what has been observed by Li et al in a Rh(III)‐catalyzed synthesis of indoles from the reactions of imidamides with diazo ketoesters via C−H activation and C−C/C−N bond cleavage . As a further aspect, in addition to 2‐phenylindoles, 2‐(naphthalene‐1‐yl)indole was also suitable for this reaction to give 3 p in 52% yield.…”
Section: Figuresupporting
confidence: 86%
“…C-Sn bond is known as a kind of very important carbon-metal bond, which has numerous applications in organic chemistry 1 , 2 , biological chemistry 3 5 , and medicinal chemistry 6 , 7 . There are three main routes for the transformation of organostannanes, including transmetalation process 8 10 , carbanion process 11 , and radical process 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…In the same year, a preparation of a polyketide precursor of aetheramides from a chiral furyl carbinol was reported by Revu and Prasad . The enantioselective total synthesis of aetheramides A and B and other stereoisomers thereof was accomplished by He et al from an achiral starting material in 15 steps and 5.3 % overall yield for aetheramide A and 3.6 % for aetheramide B . Still, in 2016 He et al reported the preparation of aetheramides A and B by using a different strategy (15 steps, 4.7 % overall yield) .…”
Section: Introductionmentioning
confidence: 99%
“…[5] The enantioselective total synthesis of aetheramides A and B and other stereoisomers thereof was accomplished by He et al from an achiral starting material in 15 steps and 5.3 % overall yield for aetheramide A and 3.6 % for aetheramide B. [6] Still, in 2016 He et al reported the preparation of aetheramides A and B by using a different strategy (15 steps, 4.7 % overall yield). [7] Three different approaches were also tested in the synthesis of the protected aetheramide by Revu and Prasad in 2017.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation